Aplikasi Pengenalan Pola Huruf Aksara Kaganga Menggunakan Jaringan Saraf Tiruan Dengan Metode Ekstraksi Fitur Geometri - Rianti, Rara Nufa (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This research aims to enable the Rejang Lebong community to relearn the Kaganga script from elementary school children to the elderly. The Kaganga script is only learned through books, teenagers or adults no longer want to learn the Kaganga script, so it is important for the Rejang Lebong people to maintain their very valuable culture. The method used is a qualitative method which is a method that focuses on in-depth observation. Data collection was carried out using an observational study conducted in the form of experimental research using a case study approach per individual for 7 (seven) image inputs consisting of 28 (two eight) Kaganga script letters to 7 (seven) different people to obtain the number of executions. The expected number of Kaganga characters is 196 letters. Testing the application by applying artificial neural networks with geometric feature extraction succeeded in character recognition of images in testing with a success rate of 92%.